Attentional modulation of neural dynamics in tactile perception of complex regional pain syndrome patients - Defina, Serena; Niedernhuber, Maria; Shenker, Nicholas; Brown, Christopher A.; Bekinschtein, Tristan A. (The European journal of neuroscience, 2021)
Body perceptual disturbances are an increasingly acknowledged set of symptoms and possible clinical markers of complex regional pain syndrome (CRPS), but the neurophysiological and neurocognitive changes that underlie them are still far from being clear. We adopted a multivariate and neurodynamical approach to the analysis of EEG modulations evoked by touch to highlight differences between patients and healthy controls, between affected and unaffected side of the body, and between “passive” (i.e., no task demands and equiprobable digit stimulation) and “active” tactile processing (i.e., where a digit discrimination task was administered and spatial probability manipulated). When correct identifications are considered, an early reduction in cortical decodability (28–56 ms) distinguishes CRPS patients from healthy volunteers. However, when error trials are included in the classifier's training, there is an unexpected increased decodability in the CRPS group compared with healthy volunteers (280–320 ms). These group differences in neural processing seemed to be driven by the affected rather than the unaffected side. We corroborated these findings with several exploratory analyses of neural representation dynamics and behavioural modelling, highlighting the need for single participant analyses. Although several limitations impacted the robustness and generalizability of these comparisons, the proposed analytical approach yielded promising insights (as well as possible biomarkers based on neural dynamics) into the relatively unexplored alterations of tactile decision‐making and attentional control mechanisms in chronic CRPS. Novel multivariate analysis of EEG signals revealed reduced neural tactile processing in complex regional pain syndrome (CRPS) patients compared with healthy volunteers (HV), between 28 and 56 ms after stimulation in passive stimulation and increased processing between 130 and 260 ms during tactile stimulation. This result partially supports the hypothesis of a worse primary sensory processing underlying perceptual disturbances in CRPS, and it points towards a higher‐order cognitive alteration that may be driven by the affected side of the body and modulated by attentional demand.